2003
DOI: 10.2741/1045
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis is associated with alterations in the relative abundance of proteins and IL-10 in the peritoneal fluid

Abstract: A growing body of evidence suggests that endometriosis modulates the microenvironment of peritoneal cavity. Therefore, in this study, we compared the protein profile of peritoneal fluids from normal fertile women with those from patients with infertility, and patients with mild to severe endometriosis. Two-dimensional gel electrophoresis of peritoneal fluids from normal subjects exhibited a distinct and reproducible pattern of proteins in the size ranges of approximately 35 to 80 kD and pI close to 4.5 to 6.6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 55 publications
0
15
2
2
Order By: Relevance
“…There are many conflicting reports in the literature on the analysis of the action of each cytokine in endometriosis and the clinical application of the results obtained with the measurement of these cytokines for the laboratory diagnosis of endometriosis. Punnonen et al (1996), Ho et al (1997) and Tabibzadeh et al (2003) also observed an increase in IL-10 in the peritoneal fluid of patients with endometriosis. On the other hand, in a study carried out in patients submitted to IVF, the authors concluded that IL-10 was higher in the control group comprised of fertile patients than in women with endometriosis and also in fertile patients than in women with infertility of inapparent cause, proving that Th2 response facilitates trophoblastic implantation at the beginning of pregnancy (Ginsburg et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…There are many conflicting reports in the literature on the analysis of the action of each cytokine in endometriosis and the clinical application of the results obtained with the measurement of these cytokines for the laboratory diagnosis of endometriosis. Punnonen et al (1996), Ho et al (1997) and Tabibzadeh et al (2003) also observed an increase in IL-10 in the peritoneal fluid of patients with endometriosis. On the other hand, in a study carried out in patients submitted to IVF, the authors concluded that IL-10 was higher in the control group comprised of fertile patients than in women with endometriosis and also in fertile patients than in women with infertility of inapparent cause, proving that Th2 response facilitates trophoblastic implantation at the beginning of pregnancy (Ginsburg et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…A single study involving IL-10 in cases of advanced disease showed an increase of this cytokine in the peritoneal fluid of patients with this specific type of endometriosis 31 . In the present analysis, IL-10 was higher in the peritoneal fluid of patients with ovarian endometriosis but not in those with the deep disease, irrespective of the presence of peritoneal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was some overlap between the first logistic regression model and the SVM ranking. This resulted in four mass peaks (one up-regulated: 10.109 kDa and three down-regulated: 4.279 kDa, 5.828 kDa, and 12.172 kDa) (Supplemental Fig. 1) that were selected as potential endometrial biomarkers for the diagnosis of moderate to severe endometriosis with a sensitivity of 80% and specificity of 70% (Table 2).…”
Section: Mass Peak Expression In Women With Moderate-severe Endometrimentioning
confidence: 99%
“…Protein analysis using two-dimensional gel electrophoresis or more advanced technology may represent a promising method for developing noninvasive diagnosis of endometriosis, on the basis of previous reports showing differential protein expression in women with endometriosis when compared with controls in peritoneal fluid (10,11) or in endometrium (12)(13)(14)(15). Although two-dimensional electrophoresis has high-resolution capacity, it is labor intensive and requires large quantities of intact proteins.…”
mentioning
confidence: 99%